This Was Tomorrow - Beil, Ralf; Ruhkamp, Uta; Kunstmuseum Wolfsburg (Cologne : Wienand, 2016)
Paolozzi, Eduardo ; Henderson, Nigel ; Hamilton, Richard ; A&P Smithson ; Blake, Peter ; Hockney, David ; Kitaj, R.B. ; Boshier, Derek ; Boty, Pauline ; Phillips, Peter ; Laing, Gerald ; Jones, Allen ; Self, Colin ; Haworth, Jann ; Price, Cedric ; Donaldson, Antony ; Caulfield, Patrick ; Smith, Richard ; Tilson, Joe
This book is published in conjunction with the exhibition This Was Tomorrow. Pop Art in Great Britain, Kunstmuseum Wolfsburg, 30 October 2016 - 19 February 2017
kunstcatalogus
Keywords: Verenigd Koninkrijk , Engeland; Groot-Brittannië